The Cek1‑mediated MAP kinase pathway regulates exposure of α‑1, 2 and β‑1, 2‑mannosides in the cell wall of Candida albicans modulating immune recognition. Issue 5 (3rd July 2016) - Román, E.; Correia, I.; Salazin, A.; Fradin, C.; Jouault, T.; Poulain, D.; Liu, F.-T.; Pla, J.
ABSTRACT: The Cek1 MAP kinase (MAPK) mediates vegetative growth and cell wall biogenesis in the fungal pathogen Candida albicans . Alterations in the fungal cell wall caused by a defective Cek1‑mediated signaling pathway leads to increased β‑1, 3‑glucan exposure influencing dectin‑1 fungal recognition by immune cells. We show here that cek1 cells also display an increased exposure of α‑1, 2 and β‑1, 2‑mannosides (α‑M and β‑M), a phenotype shared by strains defective in the activating MAPKK Hst7, suggesting a general defect in cell wall assembly. cek1 cells display walls with loosely bound material as revealed by transmission electron microscopy and are sensitive to tunicamycin, an inhibitor of N‑glycosylation. Transcriptomal analysis of tunicamycin treated cells revealed a differential pattern between cek1 and wild type cells which involved mainly cell wall and stress related genes. Mapping α‑M and β‑M epitopes in the mannoproteins of different cell wall fractions (CWMP) revealed an important shift in the molecular weight of the mannan derived from mutants defective in this MAPK pathway. We have also assessed the role of galectin‑3, a member of a β‑galactoside‑binding protein family shown to bind to and kill C. albicans through β‑M recognition, in the infection caused by cek1 mutants. Increased binding of cek1 to murine macrophages was shown to be partially blocked by lactose. Galectin-3 −/− mice showed increased resistance to fungal infection, although galectin-3 did not account for the reduced virulence of cek1 mutants in a mouse model of systemic infection. All these data support a role for the Cek1‑mediated pathway in fungal cell wall maintenance, virulence and antifungal discovery.